"Debriefing-on-Demand": A Pilot Assessment of Using a "Pause Button" in Medical Simulation. Issue 3 (June 2016) - McMullen, Michael; Wilson, Rosemary; Fleming, Melinda; Mark, David; Sydor, Devin; Wang, Louie; Zamora, Jorge; Phelan, Rachel; Burjorjee, Jessica E.
Abstract : Introduction: Simulation is an effective tool in medical education with debriefing as the cardinal educational component. Alternate debriefing strategies might further enhance the educational value of simulation. Here, we pilot a novel strategy that allows trainees to initiate debriefing at any point during the scenario, when they consider it necessary. Methods: With ethics approval, 8 postgraduate year 1 anesthesia residents (with no previous exposure to high-fidelity simulation) were randomly assigned to lead 2 of 8 scenarios with 2 debriefing strategies. With "debriefing-on-demand, " residents had the option to initiate debriefing at any point in the scenario by activation of a "pause button"—in addition to undergoing conventional debriefing at the end of the scenario. Those randomized to "conventional debriefing" were debriefed only at the end of the scenario. All were allocated as team leader with both debriefing strategies and as a participant in remaining scenarios. Residents provided feedback regarding each method using Likert scales and completion of open-ended statements. Results: Debriefing-on-demand was easily integrated into all scenarios, and most learners (88%) supported its use in future simulation sessions. The following 4 themes emerged from qualitative analyses: (1) improvements in the clarification and integration of knowledge, (2) reductions in stress/anxiety, (3) facilitated reflection on action, and (4) maintained realism comparable with conventional debriefing. Conclusions: Debriefing-on-demand was easily integrated into all scenarios and well received by these trainees new to simulation. Larger trials that use validated tools are needed to determine the absolute impact of debriefing-on-demand on stress levels and the overall learning value of simulation for trainees at different levels of training. Abstract : Supplemental digital content is available in the text.